Deep Breath Relaxation Training to Reduce Dysmenorrhoea Pain in Nursing Students, University of Muhammadiyah Gorontalo - Zuriati Muhamad; Pipin Yunus (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Dysmenorrhoea is one of the most common gynecological problems affecting more than 50% of women and causes an inability to perform daily activities for 1 to 3 days each month. One of the management of pain during menstruation is by relaxing deep breaths, namely by teaching clients how to do deep breaths and how to exhale slowly so as to reduce pain intensity and also increase lung ventilation and increase blood oxygenation. The purpose of this community service is to provide training to nursing students on deep breathing relaxation which can reduce menstrual pain (dysmenorrhoea). Deep breath relaxation training is carried out through the pretest stage, the training stage and the post test. There are 42 students who were given training in community service, namely nursing students from the 2016 and 2017 Muhammadiyah University of Gorontalo. The degree of dysmenorrhoea pain at the time of the pre test was mild pain 0% moderate pain as much as 81.0% and severe pain 19.0%. 9% and severe pain 19.0%. Based on the results of the training, it showed that most female students stated that this training was very useful because they gained knowledge and understanding of overcoming menstrual pain, after doing deep breathing relaxation students felt a decrease in dysmenorrhoea pain.